Problems and Challenges of Local Curriculum Development and Implementation in Nepal - Raut, Indra Raj (BARUN Journal, 2025)
This article aims to identify the problems and challenges of local curriculum development and implementation in Nepal. The data are analyzed qualitative research design using descriptive style. Primary data were generated from the local curriculum development committee, resource persons, education officers of the municipality, head teachers and teachers of the selected schools where the curriculum is implemented as samples. Secondary data used for this study were to complement the primary data. The study revealed that the provision of local curriculum exist the problems and challenges in the development and implementation at basic level schools. Teachers and head teachers are not well-informed and not acquainted with the developing guidelines of local curriculum. Similarly, they are perceived as lacking of technical knowledge in designing curricula. The challenges of curriculum development and implementation are mainly the lack of development of institutional mechanism and capabilities, the lack of competent and skilled human resources in the local body, lack of commitment, lack of competent teachers, lack of knowledge to parents and other stakeholders, lack of trained teachers, absence of a body providing technical support required for curriculum development at the local level. This has created dilemma in practicing the local curriculum at basic level school in Nepal.